Roles of novel IL-1 family (IL-36, IL-37, and IL-38) members in chronic brucellosis. (November 2020) - Hiz, Pinar; Kanbur, Ertan; Demir, Nesrin; Akalin, Halis; Cagan, Eren; Pashazadeh, Mehrdat; Bal, Salih Haldun; Tezcan, Gulcin; Oral, Haluk Barbaros; Budak, Ferah
Abstract: The secretion of interleukin (IL)-1 family cytokines is one of the most potent and earliest pro-inflammatory responses triggered by brucellosis. However, the roles of the most recently discovered IL-1 family members, IL-36, IL-37, and IL-38, in the transition into the chronic form of brucellos is remain largely unknown. Therefore, in this study, the roles of IL-36, IL-37, and IL-38 in brucella infections and their effects on the transition from the acute to chronic form of the disease were investigated. Using peripheral blood samples from 40 patients with acute brucellosis, 40 patients with chronic brucellosis, and 40 healthy control subjects, we analysed the serum concentrations of secreted IL-36, IL-37, and IL-38 using ELISA. The findings were confirmed by using RT-qPCR to analyse the mRNA levels of the genes encoding IL-36, IL-37, and IL-38 in peripheral blood mononuclear cells (PBMCs) from 10 randomly selected patients from each of the three groups. Our results showed that serum IL-37 (p < 0.001) and IL-38 (p < 0.001) concentrations were lower in patients with brucellosis than in the healthy controls. In addition, serum IL-37 and IL-38 concentrations were higher in the chronic patient group than in the acute patient group. The mRNA expression levels of IL-37 and IL1F10, genes that encode IL-38, did not affect serum cytokine secretion levels. This result suggests that the high secretion levels of IL-37 and IL-38 may be related to the progression into the chronic form of brucellosis. Our findings will aid in clarifying the mechanism of the transition of brucellosis from the acute to the chronic form of the disease.